Development of an Instrument for Teachers’ Attitudes towards Academic Supervision performed by Supervisors in Schools of Special Education - Pristiwaluyo, Triyanto; Syamsuddin, Syamsuddin (Journal of Educational Science and Technology (EST), 2021)
This study aims to develop an instrument for teachers’ attitudes toward academic supervision performed by supervisors in special education. This is an instrument development study working under the modified six-step development framework introduced by Djaali and Sumadi. The validity of the study was examined by two experts in measurements. The instrument was tested on 94 teachers in schools of special education in South Sulawesi. The validity and reliability were estimated using the confirmatory factor analysis by Lisrel program. The instrument produced from this attempt were 44 questions in a form of likert scale; the validity was 0.90 and the reliability was 0.96, and it was done under a tridimensional structure (i.e., monitoring, assessment, and coaching). The dimension of monitoring measured the execution of eight education standards observed by school supervisors. The dimension of assessment measured the performance of supervisors during a class supervision that was taught by a teacher of special education. The dimension of coaching measured the supervisors’ performance in giving motivation, delivering training, and providing feedback for teachers of special education. It was done in order to make the teachers more professional and independent in completing their tasks and responsibilities as teachers for special education. Therefore, the instrument produced from this research is expected to be able to describe the teachers’ attitudes toward academic supervision performed by the school supervisors.